The Influence of the Duration of Acute Coronary Syndrome on the Outcomes of Endovascular Treatment - Salo, Sergii V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Multicenter studies have proven the high effectiveness of percutaneous coronary intervention (PCI) in terms of restoring patency of the infarct-related artery (IRA) and improving the prognosis in acute myocardial infarction (AMI). The mechanism of improvement of clinical result after PCI procedure appears to be multifactorial. The aim. To investigate the effect of IRA stenting on the clinical course, prognosis and contractility of the heart in patients with different duration of acute myocardial infarction and its influence on the short-term and long-term effects after intervention. The main determinant for the favorable clinical course and improvement of the prognosis is early (within the first hours of the disease) restoration of antegrade blood flow by IRA stenting. Thus, it is possible to signifi-cantly improve the blood supply to the peri-infarct zone and limit the area of necrosis and maintain heart rate. Materials and methods. The analyzed group included 684 patients with AMI who were endovascularly treated at the Department of Emergency Endovascular Heart Surgery of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from January 1, 2017 to January 1, 2021. Coronary artery stenting was performed in all the patients. STEMI occurred in 495 (72.4%) patients, and non-STEMI in 189 (27.6%) patients. The mean age of the subjects was 61.8 ± 12.1 years. There were 289 women (42.3%) and 395 men (57.7%). Distribu-tion of the patients depending on the initial Killip class was as follows: 13 (1.9%) had class I, 199 (29.1%) had class II, and 472 (69.0%) had class III myocardial infarction. Atrial fibrillation occurred in 72 (10.5%) patients. Echocardiographic parameters were as follows: left ventricular (LV) end-systolic index 54.1 ± 12.8 ml/m2, LV ejection fraction 0.53 ± 0.05, left atrial diameter 39.5 ± 3.8 mm, systolic pulmonary artery pressure 44.8 ± 7.8 mmHg. In this study, clinical condition and functional capacity of the heart muscle in patients with AMI depending on the condition of the stent segment and the timing of endovascular procedures after the onset of the disease were first inves-tigated in the long term. Conclusions. High efficiency and safety of PCI have been proven, which makes it possible to recommend this pro-cedure for wide application. It has been proven that PCI using matrix and modular stents, as well as statins can reduce the frequency of in-stent stenosis and improve the clinical course of the disease in the long term. It has been proven that stenting in patients with AMI is most effective in the earliest stages of the disease with preservation of LV contractility with possibly complete myocardial revascularization, which contributes to the preservation of viable myocardium in the peri-infarct zone, improvement of myocardial contractility and prevention of myocardium remodeling.